Transversal communication, diaspora, and the Euro-Kurds - SOGUK, NEVZAT (Review of international studies, 2008)
The International Relations discipline (IR) has been uniquely resistant to practices and knowledges aimed at broadening the horizons of IR’s subjects. The discipline has worked to incarcerate its subjects in a location of analysis – spatially Cartesian and politically state-oriented – conditioned to ignore the transnational and transversal formations that have become central to politics. However, this disciplining has also engendered counter-movements pressuring the well-rehearsed disciplinary horizons. This article explores such movements through the Kurdish diaspora in Europe. It regards Kurdish diasporic formations as transversal practices that communicate against the disciplinary boundaries imposed upon the political imagination through traditional IR.